Oral health concerns in India - Panchali Batra; Pratap Saini; Vijay Yadav (Elsevier, 2020)
Oral health is an integral part of general health. There are many oral health issues which are of concern to India, despite having the maximum number of dental schools in the world. Dental caries, oral cancers and periodontal diseases are areas of national oral health concern. India lacks baseline data to know the exact prevalence of oral diseases, which is the first requirement to frame any national policies or manpower allocation. India is a vast country, nations within a nation, with great diversity in eating and behavioural practices. With a population of 1.21 billion and 68.84% of population residing in villages, the strategies need to be customised based on the population subgroup. Low level of awareness, strained and skewed infrastructure and resources, lack of motivation and research and oral health policies are some major factors that need to be tackled. This paper would attempt to highlight the oral health concerns of India, lacunae in the current system and possible strategies to address these issues.